2021
DOI: 10.1016/j.ypmed.2021.106622
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the impact of COVID-19 on colorectal cancer screening: Organized service screening perspectives from the Asia-Pacific region

Abstract: Colorectal cancer(CRC) is one of the most prevalent malignancies in the Asia-Pacific region, and many countries in this region have launched population CRC service screening. In this study, CRC screening key indicators, including the FIT(fecal immunochemical test) screening rate (or participation rate) and the rate of undergoing colonoscopy after positive FIT in 2019 and 2020, were surveyed in individual countries in the Asia-Pacific region. The impact of the pandemic on the effectiveness of CRC screening was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…Based on the current scenario in our screening program, the reduction of 4∼5% in both advanced cancer and mortality would be expected. A recent modelling study also revealed a 6% lower effectiveness in reducing colorectal cancer mortality by prolonged pauses of colorectal cancer screening [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current scenario in our screening program, the reduction of 4∼5% in both advanced cancer and mortality would be expected. A recent modelling study also revealed a 6% lower effectiveness in reducing colorectal cancer mortality by prolonged pauses of colorectal cancer screening [16].…”
Section: Discussionmentioning
confidence: 99%
“…To counteract the impacts that reduced cancer screening and diagnosis may cause, the following could be implemented. First, while the central government publicly manage and fund population-based cancer screenings in many developed countries such as US, UK, Australia, and New Zealand (26)(27)(28), this may not be observed in many other countries, in which affordability for cancer screenings would diminish not only during the pandemic but also during the new normal due to reduced income among the population (28). Therefore, in such countries, the central government should not solely be the key cancer screening organizer but likewise play a central role in mobilizing resources necessary for effective planning and implementation of cancer screening programs (29).…”
Section: What Can Be Done To Counteract the Impactsmentioning
confidence: 99%
“…We conducted three sensitivity analyses. First, in line with previous literature [23,24], we assumed a 10 percentage point lower participation to FIT screening during the second half of 2020 and the full year of 2021 for all strategies (i.e. in the Netherlands, overall FIT participation rate is ±73%, and now assumed to be 63%).…”
Section: Sensitivity Analysesmentioning
confidence: 99%